Space restrictions in paper and electronic dictionaries and their implications for the design of production dictionaries - Lew, Robert (My University, 2011)
One important consideration in dictionary-making has been that of space. To conserve space in paper dictionaries, a number of principles, strategies and conventions have been employed. With the gradual transition of the dictionary to the electronic medium, some of these strategies and conventions have lost, or changed, their significance. For one thing, it is no longer sufficient to speak of dictionary space alone, as was customary with paper dictionaries. One should now distinguish between at least two types of space: storage space and presentation space. In fact, this distinction is also valid for paper dictionaries. By storage space I mean the capacity to hold the total content of the dictionary. Storage space restrictions are no longer a major concern in electronic dictionaries except for the most spaceconsuming content, such as high-resolution video. Presentation space refers to the display of lexicographic information, and here the restrictions are very real in the case of electronic dictionaries. The (potentially) dynamic character of lexicographic presentation in electronic dictionaries redefines classical metalexicographic notions, such as microstructure and access structure, or entry element and cross-reference. The move of dictionaries to the electronic medium has also opened up new possibilities for dictionaries designed specifically to aid production in the second/foreign language. I offer some suggestions on how these new proposals could be improved to take advantage of the electronic medium.
This is a preprint version of: Lew, Robert (to appear - 2011?). ‘Space Restrictions in Paper and Electronic Dictionaries and Their Implications for the Design of Production Dictionaries’ in Bański, Piotr and Beata Wójtowicz (eds.), Issues in Modern Lexicography. München: Lincom Europa.
Keywords: Dictionaries; Space; Storage space; Presentation space; Electronic dictionaries; Cross-reference; Dictionaries for production